The Balanced Budget - Burkhead, Jesse (Quarterly Journal of Economics, 1954)
Introduction, 191. — I. Views of the classical economists, 192. — II. Major characteristics of Keynesian thinking about national debt and deficits, 206. — III. Reasons for slight Keynesian impact on prevalent attitude towards government debts and deficits in this country, 210; reasons for widespread acceptance of doctrine of balanced budgets for the federal government, 212.